2006
DOI: 10.14712/18059694.2017.127
|View full text |Cite
|
Sign up to set email alerts
|

IMRT with the Use of Simultaneous Integrated Boost in Treatment of Head and Neck Cancer: Acute Toxicity Evaluation

Abstract: Acute toxicity has been evaluated in head and neck cancer patients treated with intensity-modulated radiotherapy using simultaneous integrated boost (SIB-IMRT). The basis of the treatment protocol is an irradiation in 30 fractions with a total dose: 66 Gy to the region of macroscopic tumor, 60 Gy to the region of high-risk subclinical disease and 54 Gy to the region of low-risk subclinical disease. Between December 2003 and September 2005, 38 patients with carcinoma of different locations in the head and neck … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The chemotherapy used for each patient is shown in Table 1. The details of SIB-IMRT have been discussed previously (10,11). In this work, PTV, PTV-INT, and PTV-LOW prescribed radiation doses were 66, 60, and 54 Gy in 30 fractions, respectively.…”
Section: Chemotherapy and Sib-imrtmentioning
confidence: 89%
“…The chemotherapy used for each patient is shown in Table 1. The details of SIB-IMRT have been discussed previously (10,11). In this work, PTV, PTV-INT, and PTV-LOW prescribed radiation doses were 66, 60, and 54 Gy in 30 fractions, respectively.…”
Section: Chemotherapy and Sib-imrtmentioning
confidence: 89%
“…A third study, evaluating 38 head and neck cancer patients treated with radiotherapy +/− chemotherapy, reported that all patients had some degree of dysgeusia although the grade of dysgeusia was never reported as severe [32].…”
Section: Combined Modality Therapy (Rt +/− Ct)mentioning
confidence: 99%
“…In addition to better sparing of normal tissues, IMRT also allows escalating the radiation dose selectively to sub-volumes of the tumour. Simultaneously Integrated Boost technique (SIB-IMRT) is well described and evaluated especially regarding its acute and late toxicity [ 9 , 30 , 49 51 ]. This is true for salivary glands and for the mucosa [ 22 24 , 27 , 52 54 ].…”
Section: Discussionmentioning
confidence: 99%